Intimate Partner Violence and Pregnancy Termination Among Women in Sub-Saharan Africa - Arthur-Holmes, Francis (Journal of interpersonal violence, 2023)
Intimate partner violence (IPV) is predominant in sub-Saharan Africa (SSA) and has serious adverse effects on the physical, psychological, and reproductive health of those who experience it. For reproductive health outcomes, experiencing IPV has been linked to higher odds of unintended pregnancies that can result in abortion. Hence, we examined the association between IPV and pregnancy termination among women in SSA. This study used data from the Demographic and Health Surveys (DHSs) of 25 countries in SSA, which adopted a cross-sectional study design. Bivariable and multivariable binary logistic regression models were used to examine the association between IPV and pregnancy termination. The results were presented as crude odds ratios (cORs) and adjusted odds ratios (aORs), with 95% confidence intervals (CIs). The prevalence of IPV and pregnancy termination were 40.8% and 16.5%, respectively. The odds of pregnancy termination was higher among women who had experienced IPV [cOR = 1.57, 95% CI = 1.52–1.61] compared to those who had never experienced IPV. This persisted after controlling for potential confounders [aOR = 1.56, 95% CI = 1.51–1.61]. At the country level, IPV had a significant association with pregnancy termination in all the countries considered, except Sierra Leone and Namibia. These findings highlight the need for laws and policies to protect women from IPV in SSA, especially in the countries that recorded higher odds of IPV and pregnancy termination.